Minat Baca Pemustaka Di Perpustakaan IAIN Purwokerto - Indah Wijaya Antasari (AL Maktabah, 2017)
This study aims to determine the level of  reading interest for user library  in IAIN Purwokerto. Reading is a very important activity in education, especially in college. IAIN Purwokerto as part of the university has the task of educating the nation's life that can be started by reading. This study uses a descriptive quantitative approach, with  populations are  library users in IAIN library Purwokerto. Sampling using slovin formula with 10% sampling error, and samples taken 100 respondents.Method of data retrieval using questionnaires, with fifteen questions that have been validated and has a high reliability of 0.855. The results of this study indicate that the level of interest in reading librarian library IAIN Purwokerto considered good, because the average value obtained is 2.97.There are 89% of respondents who have hoby reading, 89% of respondents who like to borrow books in the library, 57% of respondents who read at least one hour a day, and 71% of respondents who set aside money to buy books.